POTENTIAL FORMATION OF ACID MINE DRAINAGE BASED ON THE GEOCHEMISTRY OF GOLD ORE ROCKS - Aminah, Siti; Haeruddin, Haeruddin; Suparno, Fanteri Aji Dharma; Irawan, Januar Fery (Universitas Medan Area, 2025)
Open pit mining activities can have many impacts on the environment, such as the formation of mine pits containing acid mine drainage. This requires proper and correct handling so as not to harm the environment. The acidity of mine drainage can vary greatly depending on the quantity and type of minerals it contains. The objectives of this research are: to identify and determine the rock materials that have the potential to generate acid mine drainage (AMD) as Potentially Acid Forming (PAF) rocks and Non-Acid Forming (NAF) rocks. The research began with sample preparation, mineralogical analysis, AAS, static testing, and XRF testing. The research results indicate that the samples are primarily composed of quartz, with some hematite and goethite grains observed as fine, curved pore fillings. Gold (Au) is found within the mineral electrum (AuAg). The minerals present in the gold ore rocks are predominantly oxides, consisting of 84.7% SiO2, 8.23% Fe2O3, and other components. The rock samples are classified as NAF, as indicated by the paste pH analysis results of 7.05 and 6.94, total sulfur analysis values of 0.37% and 6.43%, and NAPP values of -5.1 and -3.5.